Investigating functional p38-MAPK signalling during mouse blastocyst ICM cell-fate maturation. - Hauserová, Andrea (Jihočeská univerzita, 2023)
Master's thesis describes the functional role of p38-MAPK signalling during mouse blastocyst ICM cell-fate maturation.
Investigating functional p38-MAPK signalling during mouse blastocyst ICM cell-fate maturation.
Keywords: mouse preimplantation developmental stages; the first cell-fate decision; the second cell-fate decision; p38-MAPK; immunosurgery; ICM; TE; PrE; EPI; mouse preimplantation developmental stages; the first cell-fate decision; the second cell-fate decision; p38-MAPK; immunosurgery; ICM; TE; PrE; EPI